Concurrent Radiotherapy with Carboplatin and Cetuximab for the Treatment of Medically Compromised Patients with Locoregionally Advanced Head and Neck Squamous Cell Carcinoma - Saigal, Kunal; Santos, Edgardo S.; Tolba, Khaled; Kwon, Deukwoo; Elsayyad, Nagy; Abramowitz, Matthew C.; Mandalia, Amar; Samuels, Michael Andrew (Frontiers in Oncology, 2014)
Background: Cetuximab (Cx) + radiation therapy (RT) is well-tolerated and has improved survival in patients (pts) with locoregionally advanced head and neck squamous cell carcinomas (LA-HNSCC). However, its efficacy when compared to HD-DDP + RT has been questioned. At our institution, low-dose weekly carboplatin is added to Cx + RT for patients unsuitable for HD-DDP. Methods: We reviewed records of 16 patients with LA-HNSCC treated with definitive Cx + carboplatin + RT at the University of Miami from 2007 to 2011. Median follow-up was 24 months (range: 1–69 months). Results: Median age: 71.5 years (range: 57–90 years); 15 male, 1 female. ECOG PS 0 = 15, 1 = 1. TNM staging was: T1 = 1, T2 = 5, T3 = 8, T4 = 2; N stage: N0 = 8, N1 = 5, N2a = 2, N2b = 1. All patients received weekly carboplatin (AUC 1.5–2), Cx given conventionally and daily conventionally fractionated RT. Median total weeks of concurrent systemic therapy = 7 (range: 3–8 weeks). RT was delivered to a median total dose of 70 Gy (range 30–74 Gy). Of the 15 evaluable patients, there were: 12 CR, 2 PR, and 1 PD. There were three local in-field failures, two regional failures, and three distant failures. At last follow-up, 8/15 patients remained with NED. Three-year locoregional recurrence was 28.3% (95% CI: 7.7–53.9%). Mean percentage of weight loss was 14% (range: 6–26%). Two patients required systemic therapy dose reduction. Three patients experienced a treatment delay and three did not finish RT as planned including a patient who received only 30 Gy due to death secondary to MI during treatment. Conclusion: In this small retrospective series, carboplatin/Cx/RT was well-tolerated and efficacious in patients unsuitable for HD-DDP having LA-HNSCC. Acute toxicities were similar to Cx + RT, likely due to the non-overlapping toxicity profiles of the two systemic agents. We hypothesize that the addition of a well-tolerated cytotoxic chemotherapy agent may improve the therapeutic ratio of Cx + RT in patients who are poor candidates for more aggressive therapies and warrants evaluation in a prospective manner.